Focused ultrasound to diagnose HIV-associated tuberculosis (FASH) in the extremely resource-limited setting of South Sudan: a cross-sectional study. Issue 4 (2nd April 2019) - Bobbio, Flavio; Di Gennaro, Francesco; Marotta, Claudia; Kok, John; Akec, Gabriel; Norbis, Luca; Monno, Laura; Saracino, Annalisa; Mazzucco, Walter; Lunardi, Marta
Abstract : Objective: Our cross-sectional study aimed at evaluating the diagnostic performance of Focused Assessment with Sonography for HIV-associated tuberculosis (FASH) to detect extrapulmonary tuberculosis in extremely resource-limited settings, with visceral leishmaniasis as a differential diagnosis with overlapping sonographic feature. Design: Cross-sectional study. Setting: Voluntary Counselling and Testing Centre (VCT) of Yirol Hospital, South Sudan. Participants: From May to November 2017, 252 HIV-positive patients out of 624 newly admitted to VCT Centre were registered for antiretroviral treatment. According to the number of trained doctors available to practise ultrasound (US) scan, a sample of 100 patients were screened using the FASH protocol. Interventions: Following a full clinical examination, each patient was scanned with a portable US scanner in six different positions for pleural, pericardial, ascitic effusion, abdominal lymphadenopathy and hepatic/splenic microabscesses, according to the FASH protocol. A k39 antigen test for visceral leishmaniasis was also performed on patients with lymphadenopathy and/or splenomegaly. All demographic, clinical and HIV data, as well as FASH results and therapy adjustments, were recorded following the examination. Results: The FASH protocol allowed the detection of pathological US findings suggestive of tuberculosis in 27 out of the 100 patients tested. Overall, FASH results supported tuberculosis treatment indication for 16 of 21 patients, with the treatment being based exclusively on FASH findings in half of them (8 patients). The group of FASH-positive patients had a significantly higher proportion of patients with CD4 count below 0.2 x10 9 /L (n=22, 81%) as compared with FASH-negative patients (n=35, 48%) (p=0.003). Moreover, 48% (n=13) of FASH-positive patients had CD4 below 100 cells/mm 3 . All patients tested had a negative result on k39 antigen test. Conclusion: FASH was found to be a relevant diagnostic tool to detect signs of tuberculosis. Further research is needed to better define a patient profile suitable for investigation and also considering diagnostic accuracy.